KINERJA ENVIRONMENTAL, SOCIAL, DAN GOVERNMENT (ESG) DAN COST OF DEBT: APAKAH KARAKTERISTIK DEWAN KOMISARIS MEMILIKI PERAN? - Pusparini, Nandya Octanti; Amanati, Hilma Tsani (Soedirman Accounting, Auditing and Public Sector Journal, 2023)
This study aims to obtain evidence of the influence of ESG performance on the cost of debt and the role of the independent committee in this relationship. The sample used consists of non-financial companies listed on the Indonesia Stock Exchange from 2011 to 2019. The final sample comprises 205 company-year observations. Data were processed using the Generalized Least Squares (GLS) method through STATA 16.0 software. The results of this study indicate that higher ESG performance leads to lower cost of debt. This suggests that creditors view ESG performance as an important practice to be implemented in a company. The study also documents findings that the independent committee does not play a moderating role in the relationship between ESG performance and the cost of debt.